Solaris™ Operating Environment Boot Camp - Rhodes, David; Butler, Dominic (Pearson, 2002)
Complete solutions for every Solaris OE sysadmin. Step-by-step solutions for every key Solaris OE system administration task From basic user administration to complex enterprise networking Filesystems, kernels, shells, Internet/DNS, email, PPP, NIS, backup/restore, and much more Extensive examples, sample output, and shell scripts Includes coverage of Solaris 8 and 9 Operating Environments You already have the man pages: what you need are the answers! With Solaris OE Boot Camp , the answers are right at your fingertips. Drawing on nearly 30 years of experience with Sun Microsystems hardware and software, David Rhodes and Dominic Butler walk you through every facet of Solaris OE system administration, from simple user management on standalone servers to building and managing a fully networked enterprise environment. Rhodes and Butler explain every task in detail-with sample commands, specific output, lists of impacted system files, and in some cases, complete shell scripts. Coverage includes: User Administration Permissions and Security Networking Filesystems, including NFS, DFS and Autofs Serial and SCSI Connections Internet and DNS Disk Quotas Shells Email Configuration and Management Backup/Restore System Boot/Halt PPP Remote Connections Kernels and Patches Naming Services and NIS Package Administration Time, Date, and NTP And much more... Whether you've been running the Solaris Operating Environment for a week or a decade, Solaris Operating Environment Boot Camp will help you do more, do it faster, and do it better!